Meningkatkan partisipasi anggota kelompok wanita tani dalam pemanfaatan lahan pekarangan di Desa Karangrejo - Dhony Hermawan Saputra (Jurnal Dedikasi Masyarakat, 2021)
Home garden farming is a significant component of initiatives in many areas to enhance family well-being. The primary issue at hand, though, is the low usage of yard space. The purpose of this service was to address this issue by enhancing the involvement of members of the Women Farmer Group (KWT) in the utilization of yard land and its influence on the financial growth of families. A participatory strategy is employed, involving training, mentorship, and granting access to sufficient resources. According to the service's statistics, KWT members are using yard land at a significantly higher rate, which benefits both family income and agricultural productivity. In addition, the involvement of KWT members also helps to raise.